If $f:[1,\; + \infty ) \to [2,\; + \infty )$ is given by $f(x) = x + \frac{1}{x}$ then ${f^{ - 1}}$ equals

  • [IIT 2001]
  • A

    $\frac{{x + \sqrt {{x^2} - 4} }}{2}$

  • B

    $\frac{x}{{1 + {x^2}}}$

  • C

    $\frac{{x - \sqrt {{x^2} - 4} }}{2}$

  • D

    $1 + \sqrt {{x^2} - 4} $

Similar Questions

State with reason whether following functions have inverse $h:\{2,3,4,5\} \rightarrow\{7,9,11,13\}$ with $h=\{(2,7),(3,9),(4,11),(5,13)\}$

If $f: R \rightarrow R$ be given by $f(x)=\left(3-x^{3}\right)^{\frac{1}{3}},$ then $fof(x)$ is ..........

If $X$ and $Y$ are two non- empty sets where $f:X \to Y$ is function is defined such that $f(c) = \left\{ {f(x):x \in C} \right\}$ for $C \subseteq X$ and ${f^{ - 1}}(D) = \{ x:f(x) \in D\} $ for $D \subseteq Y$ for any $A \subseteq X$ and $B \subseteq Y,$ then

  • [IIT 2005]

It is easy to see that $f$ is one-one and onto, so that $f$ is invertible with the inverse $f^{-1}$ of $f$ given by $f^{-1}=\{(1,2),(2,1),(3,1)\}=f$

The inverse of the function $\frac{{{{10}^x} - {{10}^{ - x}}}}{{{{10}^x} + {{10}^{ - x}}}}$ is